Downregulation of miR-142a Contributes to the Enhanced Anti-Apoptotic Ability of Murine Chronic Myelogenous Leukemia Cells - Chen, Zhiwei; Xie, Yinyin; Liu, Dan; Liu, Ping; Li, Fei; Zhang, Zhanglin; Zhang, Mengmeng; Wang, Xiaolin; Zhang, Yuanliang; Sun, Xiaojian; Huang, Qiuhua (Frontiers in Oncology, 2021)
Background: Leukemic stem cell (LSC) is thought to be responsible for chronic myelogenous leukemia (CML) initiation and relapse. However, the inherent regulation of LSCs remains largely obscure. Herein, we integratedly analyzed miRNA and gene expression alterations in bone marrow (BM) Lin-Sca1+c-Kit+ cells (LSKs) of a tet-off inducible CML mouse model, Scl/tTA-BCR/ABL (BA). Methods: Scl/tTA and TRE-BA transgenic mice were crossed in the presence of doxycycline to get double transgenic mice. Both miRNA and mRNA expression profiles were generated from BM LSKs at 0 and 3 weeks after doxycycline withdrawal. The target genes of differentially expressed miRNAs were predicted, followed by the miRNA-mRNA network construction. In vitro and in vivo experiments were further performed to elucidate their regulation and function in CML progression. Results: As a result of the integrated analysis and experimental validation, an anti-apoptotic pathway emerged from the fog. miR-142a was identified to be downregulated by enhanced ERK-phosphorylation in BA-harboring cells, thereby relieving its repression on Ciapin1, an apoptosis inhibitor. Moreover, miR-142a overexpression could partially rescue the abnormal anti-apoptotic phenotype and attenuate CML progression. Conclusion: Taken together, this study explored the miRNA-mRNA regulatory networks in murine CML LSKs and demonstrated that ERK-miR-142a-Ciapin1 axis played an essential role in CML pathogenesis.